Attention and Olfactory Consciousness - Keller, Andreas (Frontiers in Psychology, 2011)
Understanding the relation between attention and consciousness is an important part of our understanding of consciousness. Attention, unlike consciousness, can be systematically manipulated in psychophysical experiments and a law-like relation between attention and consciousness is waiting to be discovered. Most attempts to discover the nature of this relation are focused on a special type of attention: spatial visual attention. In this review I want to introduce another type of attention to the discussion: attention to the olfactory modality. I will first clarify the position of attention to smells in a general taxonomy of attention. I will then review the mechanisms and neuroanatomy of attention and consciousness in the olfactory system before using the newly introduced system to provide evidence that attention is necessary for consciousness.